One‐Step Blade‐Coated Highly Efficient Nonfullerene Organic Solar Cells with a Self‐Assembled Interfacial Layer Enabled by Solvent Vapor Annealing. Issue 8 (4th June 2019) - Lin, Yuanbao; Yu, Liyang; Xia, Yuxin; Firdaus, Yuliar; Dong, Sheng; Müller, Christian; Inganäs, Olle; Huang, Fei; Anthopoulos, Thomas D.; Zhang, Fengling; Hou, Lintao
Abstract : A pronounced enhancement of the power conversion efficiency (PCE) by 38% is achieved in one‐step doctor‐blade printing organic solar cells (OSCs) via a simple solvent vapor annealing (SVA) step. The organic blend composed of a donor polymer, a nonfullerene acceptor, and an interfacial layer (IL) molecular component is found to phase‐separate vertically when exposed to a solvent vapor‐saturated atmosphere. Remarkably, the spontaneous formation of a fine, self‐organized IL between the bulk heterojunction (BHJ) layer and the indium tin oxide (ITO) electrode facilitated by SVA yields solar cells with a significantly higher PCE (11.14%) than in control devices (8.05%) without SVA and in devices (10.06%) made with the more complex two‐step doctor‐blade printing method. The stratified nature of the ITO/IL/BHJ/cathode is corroborated by a range of complementary characterization techniques including surface energy, cross‐sectional scanning electron microscopy, grazing incidence wide angle X‐ray scattering, and X‐ray photoelectron spectroscopy. This study demonstrates that a spontaneously formed IL with SVA treatment combines simplicity and precision with high device performance, thus making it attractive for large‐area manufacturing of next‐generation OSCs. Abstract : The fabrication of efficient organic solar cells (OSCs) via the combination of one‐step doctor‐blade printing and solvent vapor annealing (SVA) is reported for the first time. SVA improves the spontaneous stratification of the interlayer between the active layer and electrode. The achieved efficiency of 11.14% is among the highest reported to date for doctor‐blade‐coated OSCs.